The "reversibility" of chronic atrophic gastritis after the eradication of Helicobacter pylori - Yang, Hang; Zhou, Xinyue; Hu, Bing (Postgraduate medicine, 2022)
Gram-negative bacterium ( ) infection is lifelong and usually acquired in childhood, which is etiologically linked to gastric cancer (GC). gastritis is defined as an infectious disease with varying severity in virtually all infected subjects. Chronic atrophic gastritis (CAG) is the precancerous condition with the decrease or the loss of gastric glands, which can further be replaced by metaplasia or fibrosis. Patients with advanced stages of CAG are at higher risk of GC and should be followed up with a high-quality endoscopy every 3 years. infection is the most common cause and its eradication is recommended, which may contribute to the regression of CAG. However, it is controversial whether CAG is reversible after eradication therapy. In the review, we discuss recent studies which provide important insights into whether CAG is "reversibility" and when it may progress into GC after eradicating .